Endoscopy Gastrointestinal Esophagogastroduodenoscopy (EGD) Profile at Primaya Bekasi Timur Hospital Period October 2021 - October 2022 - Sismanto, Bayu Aji; Fauji, Achmad; Rahmah, Nur Miladiyah (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Introduction: Esophagogastroduodenoscopy or gastroscopy is one of the types of endoscopies; the examination includes the esophagus, gastric, and duodenum. Endoscopy is a non-surgical attempt to visualize organs with abnormalities or disorders. It can also be used to obtain tissue (biopsy), remove foreign bodies in the gastrointestinal tract, and observe organs in the body. This study aims to determine the profile of gastrointestinal endoscopy in patients examined at the endoscopy unit of Primaya Hospital, East Bekasi. Methods: The type of research conducted was descriptive retrospective using secondary data in the Medical Record Installation of Primaya Hospital, East Bekasi, from October 2021 to October 2022, totaling 103 patients. Results: The results of this study showed that 51 patients (49.5%) were male, 52 patients (50.5%) were female, and the majority of the patients were aged 41-60 years as many as 44 patients, 42.7%). The most common pre-action diagnosis was dyspepsia (43 patients, 42%), and the most common post-action diagnosis (21 patients, 20.6%) was erosive gastroduodenitis. The most common location of findings in the corpus was 33 patients (32.1%), and the most common finding was mucosal erosion in 36 patients (35.0%). Biopsy was performed in 30 patients (29.1%), and anatomical pathology revealed Helicobacter pylori in 5 patients, chronic duodenitis in 4 patients, chronic gastritis in 19 patients, chronic gastroduodenitis in 1 patient, and polyp putz jeers in 1 patient. And with the most prolonged duration of action being 10-30 minutes, namely 91 patients (88.3%). Conclusion: The results of this study indicate that chronic gastritis accompanied by H.pylori infection is a diagnosis that is more commonly found through esophagogastroduodenoscopic examination and the results of anatomical pathology examination of biopsy tissue compared to other diagnoses.